1973
DOI: 10.1139/m73-066
|View full text |Cite
|
Sign up to set email alerts
|

Derepression of a proline transport system in Staphylococcus aureus

Abstract: Staphylococcus aureus ATCC 6538P is auxotrophic tor proline. Under conditions of proline starvation, the organism synthesizes a transport system thus greatly increasing the rate of transport of proline into the cell. The proline transport systems of both the starved and unstarved cells were shown to be enzymatic, energy dependent, and specific for L-proline. Protein synthesis was required for derepression, and when the cells were fully induced, the organism established a non-exchangeable pool for proline, whos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
1996
1996

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Interestingly, in this connection, one of the characteristics of stationary phase bacteria, which can be regarded as bacteria starved for nutrients (Kolter et al ., 1993), is that glucose and amino acid transport systems are induced during starvation (Faquin & Oliver, 1984; Kolter et al ., 1993). Obbink & Campbell (1973) described increased proline transport in proline-starved S. aureus and Townsend & Wilkinson (1992) showed that strain 8325 Pro + had 3–5 times the activity of the high affinity proline transport system compared to strain 8325. Arginine and ornithine utilization is defective in B. suhtilis sigL mutants (Debarbouille et al ., 1991).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, in this connection, one of the characteristics of stationary phase bacteria, which can be regarded as bacteria starved for nutrients (Kolter et al ., 1993), is that glucose and amino acid transport systems are induced during starvation (Faquin & Oliver, 1984; Kolter et al ., 1993). Obbink & Campbell (1973) described increased proline transport in proline-starved S. aureus and Townsend & Wilkinson (1992) showed that strain 8325 Pro + had 3–5 times the activity of the high affinity proline transport system compared to strain 8325. Arginine and ornithine utilization is defective in B. suhtilis sigL mutants (Debarbouille et al ., 1991).…”
Section: Resultsmentioning
confidence: 99%